Behaviour of timber beams jointed using bonded-in pultruded rods / Nurul Izzatul Lydia Za’ba - Za’ba, Nurul Izzatul Lydia (2014)
The failure in wood structure is mainly caused by the improper connection design, construction (fabrication) detail, or serviceability. Besides using traditional bolting methods such as nails, screws and bolts to joint members, timber members can also be joined by using adhesive bonded-in rods. The advantages of using bonded-in joints are, they are stiff connection as the rods are loaded in the axial direction, good fire properties as the rod is embedded in the timber and has a high local force transfer. Research on bonded-in timber connections has been explored quite extensively in European countries. United Kingdom, and Canada using their timber, however there are no publications available on the study of bonded-in timber connections manufactured using Malaysian tropical timber. If available, mainly on the strengthening of timber beams using steel plate and carbon fibre plate. This study investigates the performance of bonded-in rod into timber as connections by exploring the effect of few parameters such as rod types (GFRP and Steel), timber types (Kempas and Keruing), diameter of rod (12mm and 8mm), adhesive types (Sikadur and Morstrong), thickness of gluelines (2mm, 3mm and 4mm) and embedded length (100mm, 150mm, 200mm, 250mm and 300mm). The test was investigated using pullout test and four point bending test. Influence of the embedded length is clearly seen as the embedded length increases, the shear strength also increases. However after the rod embedded length had reached half o f the timber length, the shear stress seems to decrease. The presence of bonded-in rod are also improved the ductility of the beam.